Sacredness of the Landscape of Vokė River in the Geography of Tatar Life Stories - Leparskienė, Lina (Lietuvos istorijos studijos, 2023)
The cultural landscape of the Vokė River (the right confluent of Neris) in the article is approached as sacred space for local Lithuanian Tatars, who have settled near this river in the end of the 14th century. There are many Tatar origin place names along Vokė, indicating how densely the area was inhabited by this Muslim community. Some villages ceased to be inhabited quite a long time ago, although older people know the precise places of the old cemeteries and mosques that have vanished or were destroyed. In their life stories the landscape of Vokė emerged as a home of many generations, space of ancestral graves and Muslim faith, as well as a realm of peaceful neighbourhood with Christians and Jews. The life stories of the Tatars from the village of Keturiasdešimt Totorių (Old Russian – Sorok Tatary, Eng. – Forty Tatars) and former Tatar settlement of Afindeviči (now part of Grigiškės town) provided pretext to explore the given territory as spiritual realm. The sacredness in the article is seen not only as a domain of religion, but also as a behaviour, a way of thinking about oneself, others and the surrounding environment. In 2020–2022 recorded life stories are analysed in the context of Christian literature from the 17th century, when Vokė River was inscribed in the sacred Catholic geography as a meaningful landmark of pilgrimage from Vilnius to Trakai. And it was one of the factors that negatively changed attitudes towards Muslim in this epoch of Counterreformation. Cultural space of the Vokė River in the article is presented from three different perspectives. The first one belongs to the paradigm of the Catholic worldview, re- flected in the 17th century literature of the authors related to Trakai: the anti-Muslim text written by Piotr Czyżewski entitled “The Real Tatar Alfurkan Divided into 40 Parts”, the religious cycle of epodes of Mathias Casimirus Sarbievius, entitled “The Four Miles of Virgin Mary or A Joyous Public Procession to the Temple of the Virgin Mary in Trakai” and the book by the dean of Trakai Symon Mankiewicz “The Trakai Parish Church, the Miracles of Our Lady Mother of God explained, by the Priest Symon Mankiewicz of the bishopric of Samogitia diocese newly exposed to the world”. Even though this literature reflects the attitude towards Muslims of only one side, it also testifies people’s behaviour where rules dictated by culture and religion were violated when danger to health or life arose. As follows from this literature, at that time the Muslim could pray at the image of Our Lady of Trakai, and a Christian seek to cure the disease with help of Tatar ‘sorcery’. Therefore, the second perspective explores Vokė as a space that has attracted people of various denominations in search for help to recover health and spiritual state of mind thanks to knowledge and mysterious power of Tatar healers, known as ‘faldjey’ (Pol. fałdżej). The portrait and activities of probably the last faldjey from those places was illuminated by his living granddaughters, whose childhood has passed listening for incredible stories of grandfather power over demons. In the third perspective, the Vokė River valley emerges as a place of Tatar pilgrimage. The most important religious centre here is the mosque of the village of the Forty Tatars, meanwhile the memory stories reveal the importance of existing and disappeared cemeteries. Operating cemeteries are still visited during Mus- lim holidays and Ramadan, and those that have disappeared are remembered via storytelling. While moving to those places both mentally and physically, local Tatars keep ties with their living and deceased compatriots, experiencing a sense of ‘tatarness’ and resilience of identity as well as reconciliation with history and neighbourhood they were ought to live.